PENGEMBANGAN TEKNIK EXPRESSIVE WRITING DALAM BIMBINGAN KELOMPOK TERHADAP PENINGKATAN PENERIMAAN DIRI SISWA SMA DI KECAMATAN GENTENG KABUPATEN BANYUWANGI - Prasetyo, Fajar Wahyu; Purnama, Diana Septi; Wangid, Muhammad Nur; Suwarjo, Suwarjo; Pamungkas, Joko (Jurnal Muria Research Guidance and Counseling (MRGC), 2024)
The purpose of this research and development is to develop, determine the feasibility and test the effectiveness of expressive writing techniques in group guidance to improve self-acceptance. The research method used in this study is research and development (RD) with the ADDIE development model, which are analysis, design, development, implementation, and evaluation. The implementation of the research was carried out in five high schools in Genteng District, Banyuwangi Regency. The subjects of this study were 8 students. The data collection techniques and tools used were validation assessment sheets (material experts, media experts, and practitioners), interviews and self-acceptance instruments. The data analysis technique used is descriptive qualitative and descriptive quantitative analysis.  The results of the study based on the validation of material experts obtained a percentage of feasibility of 80% (feasible), 81% (feasible) by media experts, and 86% (very feasible) by practitioners / counseling teachers.  The results of the Wilcoxon test obtained a significance level of 0.012 ≤ 0.05 so that it can be stated that there are differences in pretest and posttest results in the guidance group. The results of the calculation of self-acceptance scale data in the guidance group given the expressive writing technique showed an increase of 61.17% which was included in the criteria quite effective. Thus, it means that the development of expressive writing techniques in group guidance to increase self-acceptance is feasible and effective to be implemented to the students.